New Genetic Loci Associated With Chronic Kidney Disease in an Indigenous Australian Population - Thomson, Russell J.; McMorran, Brendan; Hoy, Wendy; Jose, Matthew; Whittock, Lucy; Thornton, Tim; Burgio, Gaétan; Mathews, John Duncan; Foote, Simon (Frontiers in Genetics, 2019)
The common occurrence of renal disease in Australian Aboriginal populations such as Tiwi Islanders may be determined by environmental and genetic factors. To explore genetic contributions, we performed a genome-wide association study (GWAS) of urinary albumin creatinine ratio (ACR) in a sample of 249 Tiwi individuals with genotype data from a 370K Affymetrix single nucleotide polymorphism (SNP) array. A principal component analysis of the 249 individual Tiwi cohort and samples from 11 populations included in phase III of the HapMap Project indicated that Tiwi Islanders are a relatively distinct and unique population with no close genetic relationships to the other ethnic groups. After adjusting for age and sex, the proportion of ACR variance explained by the 370K SNPs was estimated to be 37% (using the software GCTA.31; Likelihood Ratio=8.06, p-value=0.002). The GWAS identified eight SNPs that were nominally significantly associated with ACR (p < 0.0005). A replication study of these SNPs was performed in an independent cohort of 497 individuals on the eight SNPs. Four of these SNPs were significantly associated with ACR in the replication sample (p<0.05), rs4016189 located near the CRIM1 gene (p=0.000751), rs443816 located in the gene encoding UGT2B11 (p=0.022), rs6461901 located near the NFE2L3 gene and rs1535656 located in the RAB14 gene. The SNP rs4016189 was still significant after adjusting for multiple testing. A structural equation model demonstrated that the rs4016189 SNP was not associated with other phenotypes such as estimated glomerular filtration rate, diabetes and blood pressure.